Diagnóstico molecular da Leucemia viral felina por meio da utilização de Swab Oral, conjuntival e retal - Raphael Mattoso Victor (2019)
Feline leukemia virus (FeLV) infection can lead to fatal neoplasms, degenerative diseases of the hematopoietic system and immunosuppression. FeLV transmission is favored by close contact among cats that share the same space and facilities. To perform diagnostic tests, blood and its derivatives are the main specimens used currently. Blood collection, usually by venipuncture, requires physical or chemical restraint. Making diagnoses of feline retroviruses more practical and easier is crucial to reducing negative impacts on the cat’s health and will allow for an increased number of animals to be tested. The aim of this study was to evaluate the use of oral, conjunctival and rectal swab samples for the molecular diagnosis of FeLV infection. In addition to the whole blood used as reference sample, two oral swab, two conjunctival swab and one rectal swab were collected from each animal. All serum samples were submitted to immunochromatographic and PCR tests for amplification of the proviral DNA gag gene fragment. The same PCR was also performed on all swab samples. A total of 145 random animals were selected for the experiment. The occurrence of FeLV in the studied population was 49.66% by molecular diagnosis in peripheral blood mononuclear cell samples and 22.76% through the identification of the antigenemia (p27). The accuracy for each methodology evaluated was 91.72% for the PCR of samples obtained by oral swabbing; 91.23% for those from conjunctival swab and 85.50% for those obtained by rectal swabbing. The sensitivity and specificity of each PCR evaluated in relation to the reference PCR were, respectively, 86.11% and 97.26% for the oral swab PCR; 90% and 92.59% for conjunctival swab PCR; and 74.24% and 95.77% for rectal swab PCR. Kappa values for oral swab PCR, conjunctival swab PCR and rectal swab PCR were 0.89, 0.89 and 0.82, respectively. Sampling using oral, conjunctival and rectal mucosal 11 swabs for the molecular diagnosis of FeLV infection is an excellent alternative to the venipuncture, especially in places where the presence of trained and qualified professionals is limited or not available, or even for shelters with a large feline population. In addition, the methodology is faster, less laborious, less expensive and well accepted by the animal. Another relevant finding of this study was the detection of FeLV proviral DNA in oral and conjunctival mucosal cells, allowing the diagnosis of animals in the regressive phase of infection.